Liposomal photosensitizer encapsulation as a strategy to enhance antimicrobial photodynamic therapy against Candida auris biofilms - Lima, Patrícia Michelle Nagai de [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Candida auris poses a significant healthcare challenge, particularly within immunosuppressed patients. This pathogen can colonize the skin and develop biofilms associated with increased antifungal drug resistance that are difficult to treat. Some adjuvant treatments have been investigated, such as antimicrobial photodynamic therapy (aPDT), that employs a photosensitizer (PS) irradiated by light in the presence of oxygen. However, most PSs available suffer from poor biofilm penetration. This study aimed to analyze the effects of antimicrobial photodynamic therapy (aPDT) mediated by the photosensitizer methylene blue (MB), encapsulated in liposomal formulations, on C. auris biofilms. Initially, liposomes were fabricated by thin-film hydration followed by extrusion, yielding positively (MB-P) or negatively (MB-N) charged formulations. Liposomes were characterized by dynamic light scattering (hydrodynamic diameter, polydispersity index, and ζ-potential), encapsulation efficiency, and drug loading. After fabrication and characterization, the interaction of the developed formulations with C. auris (CBS 11220) in planktonic cultures and biofilms was evaluated by confocal microscopy. Subsequently, the effects of the formulations on aPDT against C. auris were studied using a 660-nm red LED and MB free or encapsulated in liposomas. Experimental conditions included NL and PL (empty liposomes), free MB, MB-P, and MB-N, each assessed with and without irradiation. The viability of fungal cells was evaluated by counting Colony Forming Units (CFU) in planktonic cultures and biofilms, as well as biomass by staining the biofilms with Crystal Violet. In addition, the production of reactive oxygen species (ROS) by C. auris cells was analyzed using H₂DCFDA fluorescence, and dark cytotoxicity toward mammalian cells was evaluated using the CCK-8 assay. The data were subjected to Analysis of Variance and Tukey's test, considering p < 0.05 as significant. The results confirmed that liposomal formulations with positive (MB-P) and negative (MB-N) charges were able to encapsulate methylene blue and provide efficient delivery to C. auris cells in planktonic cultures and biofilms. In the aPDT results, both MB-P or MB-N formulations resulted in the eradication of planktonic cells of C. auris at minimum fungicidal concentrations equivalent to free MB. MB-loaded liposomes showed enhanced penetration within biofilms and reduced C. auris biofilm burden up to 3× more compared to free MB. Additionally, biofilm biomass was reduced up to 37% with MBloaded liposomes, while free MB only achieved ~3% reduction. Furthermore, aPDT mediated by MB-P or MB-N led to the production of ROS 2× higher than free MB, leading to greater oxidative damage towards C. auris biofilms. Finally, MB-loaded liposomes maintained ~80% of fibroblasts viability compared to ~58% viability for free MB. Promisingly, MB-P and MB-N liposomes were able to enhance the in vitro activity of PDT on C. auris biofilms, inciting the development of in vivo studies to validate its efficacy and safety.

Candida auris representa uma ameaça à saúde pública, principalmente aos indivíduos imunossuprimidos. Este patógeno é capaz de colonizar a pele e desenvolver biofilmes associados com o aumento da resistência antifúngica. Tratamentos adjuvantes tem sido investigado, como a terapia fotodinâmica antimicrobiana (TFDa), que emprega o uso de um fotossensibilizador e irradiação como fonte de luz na presença de oxigênio. Entretanto, a maioria dos fotossensibilizadores apresentam baixa penetração no interior dos biofilmes. Este trabalho teve como objetivo analisar os efeitos da TFDa mediada pelo azul de metileno (AM), encapsulado em formulações lipossomais, sobre biofilmes de C. auris. Lipossomas contendo AM foram produzidos por hidratação de filme fino seguida de extrusão, resultando em formulações carregadas positivamente (AM-P) ou negativamente (AM-N). Os lipossomas foram caracterizados por espalhamento dinâmico de luz (diâmetro hidrodinâmico, índice de polidispersão e potencial-ζ), eficiência de encapsulamento e carregamento do fármaco. Após, foi avaliada a interação das formulações com as células de C. auris (CBS 11220) em culturas planctônicas e biofilmes por microscopia confocal. A seguir, foram estudados os efeitos das formulações na TFDa contra C. auris, empregando-se LED vermelho (660 nm) e AM nas formas livre e lipossomal. As condições experimentais incluíram NL e PL (lipossomas vazios), AM livre, AM-P e AM-N, cada uma avaliada com e sem irradiação. A viabilidade das células fúngicas foi avaliada pela contagem de Unidades Formadoras de Colônias em culturas planctônicas e biofilmes, além da biomassa por coloração dos biofilmes com Cristal Violeta. Além disso, foram analisadas a produção de espécies reativas de oxigênio (EROs) pelas células de C. auris utilizando a sonda H₂DCFDA, e a citotoxicidade no escuro em fibroblastos (NIH 3T3) por meio do ensaio CCK-8. Os dados foram submetidos à análise de variância e teste de Tukey, considerando p < 0,05 como significativo. Os resultados confirmaram que as formulações lipossomais com carga positiva (AM-P) e negativa (AM-N) foram capazes de encapsular o AM e proporcionar uma entrega eficiente às células de C. auris em culturas planctônicas e em biofilmes. Nos resultados da TFDa, ambas as formulações levaram à erradicação das culturas planctônicas de C. auris com concentrações fungicidas mínimas equivalentes ao de AM livre. Os lipossomas AM-P e AM-N aumentaram a penetração do AM nos biofilmes e causaram redução da viabilidade celular 3 x maior do que a TFDa mediada por AM livre. Houve também, redução de até 37% da biomassa de biofilmes tratados com as formulações lipossomais, enquanto o AM livre reduziu apenas 3%. Além disso, a TFDa mediada pelas formulações de AM-P ou AM-N levou à produção de EROs 2 x maior do que o AM livre, resultando em maior dano oxidativo aos biofilmes de C. auris. Por fim, os lipossomas carregados com AM mantiveram cerca de 80% da viabilidade celular de fibroblastos, em comparação com cerca de 58% de viabilidade para o AM livre. Os lipossomas AM-P e AM-N foram capazes de aumentar a atividade in vitro da TFDa em biofilmes de C. auris, incentivando o desenvolvimento de estudos in vivo para validar sua eficácia e segurança.
Encapsulamento lipossomal de fotossensibilizador como estratégia para aprimorar a terapia fotodinâmica antimicrobiana contra biofilmes de Candida auris
Keywords: Methylene Blue; Liposomes; Photosensitizing agents; Azul de metileno; Fármacos fotossensibilizantes; Lipossomos; Candida auris; Candida auris